2017
DOI: 10.1186/s11671-016-1822-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post Annealing Treatments on the Interfacial Chemical Properties and Band Alignment of AlN/Si Structure Prepared by Atomic Layer Deposition

Abstract: The influences of annealing temperature in N2 atmosphere on interfacial chemical properties and band alignment of AlN/Si structure deposited by atomic layer deposition have been investigated based on x-ray photoelectron spectroscopy and spectroscopic ellipsometry. It is found that more oxygen incorporated into AlN film with the increasing annealing temperature, resulting from a little residual H2O in N2 atmosphere reacting with AlN film during the annealing treatment. Accordingly, the Si–N bonding at the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Understandably, kinds of crystal defects in the ALD deposited AlN film were the main reasons. Further XPS measurement well indicated the typical O related defects (Al–O bond at binding energy of 74.6 eV and N-Al-O bond at a binding energy of 398.8 eV) for the ALD deposited AlN film, which shows similar results as that reported in the previous work 37 , 38 , as shown in Fig. 2e and f for the Al 2 p and N 1 s spectra.…”
Section: Resultssupporting
confidence: 87%
“…Understandably, kinds of crystal defects in the ALD deposited AlN film were the main reasons. Further XPS measurement well indicated the typical O related defects (Al–O bond at binding energy of 74.6 eV and N-Al-O bond at a binding energy of 398.8 eV) for the ALD deposited AlN film, which shows similar results as that reported in the previous work 37 , 38 , as shown in Fig. 2e and f for the Al 2 p and N 1 s spectra.…”
Section: Resultssupporting
confidence: 87%
“…Encouragingly, a homogeneous N-doping profile can be observed in the entire AlON film (Figure b). It is known that this kind of nitrogen distribution can hardly be achieved by the conventional growth method including annealing the ALD-grown Al 2 O 3 or AlN film in NH 3 or O 2 environment. , In addition, it is noted that the obtained AlON film is oxygen-rich, although the NH 3 :O 2 ratio is as high as 95:5 during the film growth. This is mainly due to much higher reactivity of oxygen plasma than that of the ammonia one.…”
Section: Resultsmentioning
confidence: 99%
“…13 There have been investigations on indirect growth of the AlON utilizing the ALD. 6,10,14 However, as mentioned in the last paragraph, the doping homogeneity became a problem. Theoretically, the direct growth of the AlON utilizing ALD can be achieved by alternate growth of the AlN and the Al 2 O 3 layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,40,42,43 Thus far, there have been no reports on how high temperatures affect the band offset between SiO 2 and (In x Ga 1−x ) 2 O 3 . There have been a few previous studies done examining the annealing effects of dielectrics or other semiconductors on Ga 2 O 3 and (Al x Ga 1−x ) 2 O 3 , [44][45][46][47][48][49][50] but no work has been done on (In x Ga 1−x ) 2 O 3 based systems. Yadav et al 45 found that the valence band offset between Ga 2 O 3 and Si increased with annealing at 600 °C.…”
mentioning
confidence: 99%